Through the Wheat : the U.S. Marines in World War I. - Simmons, Edwin H., 1921-2007 (Naval Institute Press, 2014)
U.S. Marine participation in World War I is known as a defining moment in the Marine Corps'' great history. It is a story of exceptional heroism and significant operational achievements, along with lessons learned the hard way. The Marines entered World War I as a small force of seagoing light infantry that had rarely faced a well-armed enemy. On a single June day, in their initial assault ""through the wheat"" on Belleau Wood against German machine-guns and poison gas shells, the Marines suffered more casualties than they had experienced in all their previous 142 years. Yet at Belleau Wood, S.